ANALISIS PENGGUNAAN MEDIA EVALUASI DARING DALAM PEMBELAJARAN DI INDONESIA - Utari Akhir Gusti (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2022)
The Covid-19 pandemic has had a huge impact on the world of education. One of them is the shift in evaluation media. This study aims to investigate online evaluation media that teachers use in learning. The research method is qualitative with an exploratory approach. Data collection techniques consist of interviews, observation, and literature study. The results of the study revealed that the media that teachers generally use in carrying out online evaluations is the Google form. Other tools used by teachers such as kahoot, quizizz, survey monkey, meter, LMS (Learning Management System). The use of this media is very helpful for teachers and students in improving their ability to use technological devices.